The Maronites - Henley, ADM (Routledge, 2018)
Maronites constitute the most politically powerful Christian community in the Middle East, despite being far from the largest, due to their overwhelming geographical concentration in one small country, Lebanon. Of Lebanon’s population of about 4.5 million, Maronites make up at least 20%, putting them in a close third place to the Sunni and Shi’i Muslim communities. 1 Hence, they constitute a numerical minority of the Lebanese, but the label ‘minority’ is arguably ill-fitting in its social, cultural, and political senses. As one of the largest of Lebanon’s eighteen state-recognized religious communities, the Maronite community is not overshadowed by any monolithic Lebanese majority. Indeed, Maronites could be said to enjoy many of the privileges we associate with majority status in this nation of minorities. They are central to the telling of Lebanese history, heavily represented in literary and popular culture, physically present both in the capital and virtually all major regions of the country (albeit with far from equal distribution), and hold a monopoly over certain key political posts including the presidency of the Republic itself. It is worth adding that while being one of three leading communities, the Maronites are also significantly the largest of Lebanon’s many Christian denominations, making them in practice the dominant spokespeople for the Christian ‘half’ of the country. 2 Far from being marginal, therefore, this small community – perhaps eight times smaller than Egypt’s Coptic Christian minority, for example – is often said to be the ingredient that makes Lebanon unique in the region: ‘a message’ or ‘an example of pluralism’ as Pope John Paul II famously called it. 3